Grinding wheels for manufacturing of silicon wafers: a literature review - Liu, J. H.; Pei, Zhijian J.; Fisher, Graham R. (My University, 2007)
Grinding is an important process for manufacturing of silicon wafers. The demand for silicon wafers with better quality and lower price presents tremendous challenges for the grinding wheels used in the silicon wafer industry. The stringent requirements for these grinding wheels include low damage on ground surfaces, self-dressing ability, consistent performance, long wheel lives, and low prices. This paper presents a literature review on grinding wheels for manufacturing of silicon wafers. It discusses recent development in abrasives, bond materials, porosity formation, and geometry design of the grinding wheels to meet the stringent requirements.
Keywords: Abrasive; Grinding wheel; Machining; Semiconductor material; Silicon wafer